The handbook of narrative analysis - De Fina, Anna; Georgakopoulou, Alexandra (Malden, MA : Wiley Blackwell, 2015)
Featuring contributions from leading scholars in the field, The Handbook of Narrative Analysis is the first comprehensive collection of sociolinguistic scholarship on narrative analysis to be published. The collection includes chapters that exhibit the latest advances in narrative analysis, from work on social media to small stories research, as well as essays that address topics traditionally shaped and influenced by narrative inquiry, such as researcher reflexivity, embodiment, story ownership, and chronotopic configurations. Organized thematically to provide a guide for approaching the stud.
5.9 Teachers and Learners -- Biographical Research5.10 Conclusion; References; Part II Time-Space Organization; Chapter 6 Narrative and Space/Time; 6.1 Introduction; 6.2 From Backdrop to Constitutive Accounts of Space/Time Orientation in Narrative; 6.3 Narratives of Border Crossing; 6.4 Deictic Transposition in Migration Narratives; 6.5 Migration from West to East in Post-Unification Germany; 6.6 Socio-symbolic Meanings of Space/Time in Narrative; 6.7 Scale and Space/Time Orientation in Narrative; 6.8 Scale and Indexicality in Narratives of Migration; 6.9 Space/Time in Language Classrooms.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Discourse analysis, Narrative -- Handbooks, manuals, etc; Narration (Rhetoric) -- Handbooks, manuals, etc; Discourse analysis, Narrative; English fiction -- History and criticism; Narration (Rhetoric); LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Discourse analysis, Narrative; Narration (Rhetoric); Diskursanalys; Narratologi; Berättande.; Electronic books; Handbooks and manuals; Electronic books